Accuracy of Neonatal Early Onset Sepsis Calculator in Predicting EOS in Neonates ≥ 34 Weeks of Gestation (Medical Forum Monthly, 2022)
Objective: To determine the accuracy of Early Onset Sepsis (EOS) risk calculator by following blood culture reports and CRP for predicting EOS in neonates with 34 weeks or more gestational age.Study Design: prospective observational studyPlace and Duration of Study: This study was conducted at the National Institute of Child Health, Karachi from April, 2022 to July, 2022.Materials and Methods: All newborns with suspected EOS presented with 34 weeks or more gestational age of either gender on empiric antibiotics during past 3 days were enrolled. Early onset neonatal sepsis risk calculator was calculated using Kaiser Permanente calculator.Results: Of 249 neonates, EOS risk calculator shows that 60 (24.1%) had clinical illness whereas 63 (25.3%) patients had well appeared status and 126 (50.1%) had equivocal status. A significantly higher risk of clinical illness was observed in low birth-weight neonates (p= 0.026), lower gestational age (p= 0.007), higher maternal temperature, having rupture of membrane (p= <0.001), higher duration of rupture of membrane (p= <0.001), GBS in any trimester (p= <0.001), >4 hours of broad-spectrum antibiotics (p= <0.001), lower oxygen saturation (p= <0.001), respiratory distress (p= 0.003), APGAR score <7 (p= <0.001), positive blood culture (p= <0.001), and positive CRP (p= <0.001).Conclusion: EOS risk calculator has highlighted around one fourth of neonates with the high risk of clinical illness in neonates presented with ≥ 34 weeks of gestational age.